Severe hyperkalemia in two renal transplant recipients treated with standard dose of trimethoprim-sulfamethoxazole - KOÇ, MEHMET (W B SAUNDERS CO, 2000)
Hyperkalemia is a serious electrolyte disorder and is a frequent finding in renal transplant recipients. Trimethoprim-induced hyperkalemia has been increasingly reported in recent years. We describe two renal transplant recipients who developed end-stage renal disease secondary to familial Mediterranean fever and presented with severe hyperkalemia secondary to the use of standard dose of trimethoprim. One of the patients had potential underlying adrenal insufficiency, which might be a contributing factor for the development of hyperkalemia. We concluded that renal transplant patients receiving even the standard dose of trimethoprim should be monitored closely for the development of hyperkalemia. They should be recognized as a group with increased risk In regard to their concurrent renal insufficiency, concomitant use of cyclosporine, and associated tubulointerstitial disease. Patients with secondary amyloidosis are at even greater risk, and subclinical adrenal insufficiency may be an underlying risk factor for the development of severe, life-threatening hyperkalemia among this group of patients. (C) 2000 by the National Kidney Foundation, Inc.
Keywords: renal transplantation; hyperkalemia; trimethoprim; amyloidosis; familial Mediterranean fever (FMF); PNEUMOCYSTIS-CARINII PNEUMONIA; CO-TRIMOXAZOLE; AMYLOIDOSIS; CYCLOSPORINE; INSUFFICIENCY; EXCRETION; MECHANISM; SECONDARY; PATIENT; THERAPY